Role of Epidural Steroid and Local Anesthetic in Post-Operative Outcome Following Lumber Discectomy - Muhammad Muzaffer Uddin, Abdul Razaque Mari, Farrukh Zulfiqar, Muhammad Munwar Ali, Qazi Muhammad Zeeshan, Ramesh Kumar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The purpose of the study was to assess the outcome of epidural infiltration of local anesthetic and steroid intraoperatively in comparison with placebo (saline) after lumbar discectomy. Study Design: A prospective double blinded randomized controlled trial conducted in a tertiary care centre over two and half years’ duration, from July 2019 to December 2021 Methods: 70 subjects enduring lumbar discectomy were randomised to the intraoperative infiltration of triamcinolone acetonide (40mg/ml, 2ml) and bupivacaine (0.5%, 3ml) in A group or B group who were given equal (5ml) volume of normal saline. Infiltration was achieved after decompression and discectomy, and just before the incision was closed. In the postoperative period, the standard procedure of physiotherapy and intravenous paracetamol administration were used. Supplementary analgesics with tramadol was used solitary in patients requiring greater pain control. The VAS scale was used to access pain post-operatively and use of opioids was documented. Primary outcomes measures included immediate post-operative VAS back pain, infection rate and opioid use. The subjects were reassessed at six-weeks and three months after surgery. Results: No patient in A group needed opioid analgesic while 14 patients in group B needed additional tramadol as a pain killer for pain relief (p = 0.01). At the third hour after surgery, the VAS result was lower significantly in A group in comparison to the group B (p <0.05). No infection or other serious complication was reported and no revision surgery was performed in either group. One patient in each group stated residual radiculopathy, but after 6 weeks both patients’ symptoms resolved. Conclusions: Intraoperative administration of local anaesthetics and steroids is fruitful in reducing pain only for a brief time afterwards the surgical procedure, without affecting the infection rate and long-standing outcomes in comparison to the placebo.